Covid-19 Pandemic and African Autochthonous Development Challenges. - ABANEME, Ambrose O.; EJIEJI-EZEIBE, Peace Ijeoma; MICHAEL, Maureen Chinenye (Socialscientia: Journal of Social Sciences and Humanities, 2022)
This paper evaluates the impacts of covid-19 pandemic on African socio-economic development challenges. The paper relies on secondary sources of data which build upon the dependency paradigm and argues that the lessons from the pandemic shock exposed the danger of Africa’s dependent economy. This study thereafter concludes by advocating that Africa should prioritize their socio-economic development policies into autochthonous strategies. Lastly, the paper recommends amongst others, that the implementation of the African Continental Free Trade Area (AICFTA) will be decisively crucial in diversifying African economies which provides a shield from such global stocks that impact on the direction of socio-economic progress of Africa.